Informations récentes sur la responsabilité des produits : partie 1 - Asselin, André (Assurances, 1994)
In his attempts to bring the rules of product liability from craftsmanship to nuclear age, the New Civil Code of Quebec might have troubled quiet waters. The author reviews the relevant sections of the New Code in that respect, and their roots in jurisprudence. ln the second part, to be published in the next issue, he will examine the effects of the brand-new approach in the code to the rules of Conflicts of Law.